Bacterial versus human thymidylate synthase: Kinetics and functionality - Islam, Zahidul; Gurevic, Ilya; Strutzenberg, Timothy S.; Ghosh, Ananda K.; Iqbal, Tasnia; Kohen, Amnon (PLOS ONE, 2018)
Thymidylate Synthase (TSase) is a highly conserved enzyme that catalyzes the production of the DNA building block thymidylate. Structurally, functionally and mechanistically, bacterial and mammalian TSases share remarkable similarities. Because of this closeness, bacterial enzymes have long been used as model systems for human TSase. Furthermore, while TSase inhibitors have long served as chemotherapeutic drugs, no TSase inhibitor serves as an antibiotic. Despite their high resemblance, the mammalian TSases are distinct in a few known aspects, such as having a N-terminal tail and two insertions in the primary sequence and active/inactive conformations. Here, we aim to comprehensively characterize human (hs) TSase and delineate its contrasts and the similarities to the well-studied Escherichia coli (ec) TSase. We found that, in contrast to ecTSase, Mg2+ does not enhance reaction rates for hsTSase. The temperature dependence of intrinsic kinetic isotope effects (KIEs), on the other hand, suggests that Mg2+ has little or no impact on the transition state of hydride transfer in either enzyme, and that the transition state for the hydride transfer in hsTSase is looser than in ecTSase. Additionally, the substrates’ binding order is strictly ordered for ecTSase but slightly less ordered for hsTSase. The observed kinetic and functional differences between bacterial and human enzymes may aid in the development of antibiotic drugs with reduced toxicity.